The Impact of Perceived High Performing Work Practices on Employee Engagement: A Study on Multinational Corporations Operating in Sri Lanka - Jayarathna, S.M.D Yasodara; Shermila, K.A Udeni (Asian Journal of Empirical Research, 2018)
Investigating the impact of perceived high performing work practices (HPWP) on employee engagement (EE) in multinational corporations (MNCs) operating in Sri Lanka is the main purpose of this study. There was very few research studies conduct to estimate this relationship, yet none examines the impact of perceived HPWP on dimensions of employee engagement; vigor, dedication and absorption. A self-administered questionnaire, which developed using standard measures, and distributed employees above executive level in MNCs. The data were collected from 348 employees. Finding reveals a positive impact of perceived HPWP on employee engagement and with each dimension; vigor, dedication and absorption. The study contributes to employee engagement and high performance work practices literature by focusing on an untouched area.